2017
DOI: 10.1039/c7cp00188f
|View full text |Cite
|
Sign up to set email alerts
|

Modification of N-doped TiO2 photocatalysts using noble metals (Pt, Pd) – a combined XPS and DFT study

Abstract: Nitrogen-doped TiO (N-TiO) is considered as one of the most promising materials for various photocatalytic applications, while noble metals Pd and Pt are known as good catalysts for hydrogen evolution. This work focuses on the determination of structural and electronic modifications of N-TiO, achieved by noble metal deposition at the surface, as a starting indicator for potential applications. We focus on the properties of easily synthesized nanocrystalline nitrogen-doped anatase TiO, modified by depositing sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 66 publications
5
27
0
Order By: Relevance
“…Here, our N-doped P25 samples showed better absorption compared with the P25-UN showing that N doping gives successful visible light absorption. Similar to other studies in the literature, we observed a better light absorption in the visible range for our N-doped [ 27 , 42 ] and F-doped samples [ 28 ]. Moreover, P25-F-HT and P25-F&N-HT showed a similar trend for the same anatase-to-rutile ratio.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Here, our N-doped P25 samples showed better absorption compared with the P25-UN showing that N doping gives successful visible light absorption. Similar to other studies in the literature, we observed a better light absorption in the visible range for our N-doped [ 27 , 42 ] and F-doped samples [ 28 ]. Moreover, P25-F-HT and P25-F&N-HT showed a similar trend for the same anatase-to-rutile ratio.…”
Section: Resultssupporting
confidence: 91%
“…All of these results showed that doped samples changed the electronic structures of P25 that were associated with lower band gap energy. Similar modifications in the adsorption spectra have been previously observed for N and F monodoped anatase nanoparticles [ 42 , 53 ]. However, it was found that F&N modification considerably enhanced the visible light absorption of TiO 2 as observed in our experiments [ 34 , 54 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The peak at 399.1 eV demonstrated that nitrogen is incorporated into the TiO 2 lattice. This considered to be the evidence of the presence of the Ti–N bond 32 .…”
Section: Resultsmentioning
confidence: 97%
“…It has to be pointed out that nitrogen incorporation in the Ns form (BE~396 eV) is only reported for a few instances of nitrogen and metal ions co-modified, titania obtained by the sol-gel method (using urea and RuCl 3 [39], ammonia and Sr(NO 3 ) 2 [43], dodecylamine and Fe(NO 3 ) 3 •9H 2 O [44], tetramethylethylenediamide and Pt 0 /Pt 2+ [45]). Additionally, N1s lines with BE at 397.5 defined by XPS in the samples obtained by the solvothermal method using urea and H 2 PtCl 6 are also reported [46]. Thus, the possibility of N to be incorporated in Ns and Ni forms by means of the sol-gel technique depends on the nature of the co-doped metal ions.…”
Section: Platinummentioning
confidence: 87%